2016
DOI: 10.1038/ncomms10999
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-based multi-element chemistry for grid-scale electrochemical energy storage

Abstract: Calcium is an attractive material for the negative electrode in a rechargeable battery due to its low electronegativity (high cell voltage), double valence, earth abundance and low cost; however, the use of calcium has historically eluded researchers due to its high melting temperature, high reactivity and unfavorably high solubility in molten salts. Here we demonstrate a long-cycle-life calcium-metal-based rechargeable battery for grid-scale energy storage. By deploying a multi-cation binary electrolyte in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 16 publications
1
71
0
6
Order By: Relevance
“…Moreover, the Ca-Mg alloy of low Ca concentration decreased the solubility of Ca in the molten salt by almost two orders of magnitude (see Figure 16d). More recently, Ouchi et al [80] reported a Ca-Mg | LiCl-CaCl 2 | Bi cell, operating at 550 °C, achieving 99% of Coulombic efficiency and excellent cycling performance, which further confirmed the above results.…”
Section: Calcium-based Systemssupporting
confidence: 82%
“…Moreover, the Ca-Mg alloy of low Ca concentration decreased the solubility of Ca in the molten salt by almost two orders of magnitude (see Figure 16d). More recently, Ouchi et al [80] reported a Ca-Mg | LiCl-CaCl 2 | Bi cell, operating at 550 °C, achieving 99% of Coulombic efficiency and excellent cycling performance, which further confirmed the above results.…”
Section: Calcium-based Systemssupporting
confidence: 82%
“…Temperatures much higher than 450 °C are required for liquid‐metal batteries, which comprise a liquid‐metal anode, a liquid‐metal cathode, and a molten salt electrolyte of mixed‐metal halides . For example, a Ca‐Mg (90–10 mol %)∥Bi electrochemical couple was operated in an electrolyte of molten LiCl‐CaCl 2 at 550 °C and showed a high capacity‐retention rate and Coulombic efficiency over 1400 cycles . The electrodes and electrolyte self‐segregated by density into three distinct layers because of the immiscibility of the electrolyte salt and metal phases.…”
Section: Introductionmentioning
confidence: 99%
“…The specific energy of the MIB is comparable to that of the LIB and whilst the specific power of the MIB matches that of electrochemical capacitors. [33][34][35] When inexpensive carbonates,s uch as Na 2 CO 3 ,K 2 CO 3 ,a nd KCl were substituted for Li 2 CO 3 ,t he cost of molten salt would be significantly decreased. [10,32] Undoubtedly, the superior performance of the MIB derives from the ultrafast redox reactions at high temperatures.…”
Section: Discussionmentioning
confidence: 99%